(untitled) (Вісник: Міжнародні відносини, 2025)
Food safety, nutritional value and food security are interrelated concepts. The consumption of unsafe foods contributes to disease and malnutrition, especially among vulnerable groups such as infants, children, the elderly and those with compromised immune systems. In addition to its impact on health, food safety contributes to economic growth, tourism and international trade, which are important factors for sustainable development. Food security is also affected by market globalization, demographic change, environmental challenges and the transformation of food systems. The identification of product quality indicators with indicators of current standards often indicates a decrease in the nutritional value of food products and an excess of the maximum content of a contaminant in the product, which does not allow it to be classified as a safe product. In turn, a safe food product is a food product that does not create a harmful effect on human health directly or indirectly under the conditions of its production and circulation in compliance with the requirements of sanitary measures and consumption for its intended purpose.